2022
DOI: 10.3390/healthcare10091728
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Assessment of Complementary and Alternative Medicine (CAM) Use among Patients with Chronic Diseases (CDs) in Qassim, Saudi Arabia

Abstract: This study aims to investigate CAM use among CD patients from Qassim, Saudi Arabia and to compare CAM practice with different demographic and disease characteristics of the participants. A cross-sectional study was conducted among CD patients. During the three-months of data collection period, a total of 377 patients were approached and 208 patients participated in the study, giving a response rate of 55.17%. A p value of <0.05 was considered as significant. Among the study population, 94 (45.2%) patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
9
1
Order By: Relevance
“…This is consistent with other studies showing females were more likely to use CAM [21,[23][24][25]. Also, other studies have shown that higher education might be associated with CAM use [18,21]. Nevertheless, in one qualitative study, the education level of parents was not associated with use of CHA for their children [17].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with other studies showing females were more likely to use CAM [21,[23][24][25]. Also, other studies have shown that higher education might be associated with CAM use [18,21]. Nevertheless, in one qualitative study, the education level of parents was not associated with use of CHA for their children [17].…”
Section: Discussionsupporting
confidence: 88%
“…This suggests that most of the participants from KSA are aware enough not to use CAM interventions without an appropriate consultation. A few studies reported that almost half of CAM users consulted with or disclosed to physicians about the use of CAM [19][20][21]. Unwillingness to stop using CAM was one of the most common reasons for non-disclosure [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Qassim region of Saudi Arabia, spiritual therapies (26.59%) were the most common CAM used among hypertensive patients followed by herbal products (15.95%). In general, between 8% and 76% of Saudi Arabians have been reported use H (Farooqui et al, 2022). In Asir region, honey and olive oil were most frequently used (78.7%), followed by herbs (47.8%) (Dalia et al, 2021) The majority of participants mostly turned to their relatives and friends for information.…”
Section: Discussionmentioning
confidence: 99%